Oxygen uptake kinetics and biological age in relation to pulling force and 400-m front crawl performance in young swimmers - Strzała, Marek; Sokołowski, Kamil; Wądrzyk, Łukasz; Staszkiewicz, Robert; Kryst, Łukasz; Żegleń, Magdalena; Krężałek, Piotr; Maciejczyk, Marcin (Frontiers in Physiology, 2023)
The study aim was to assess differences in the biological age (BA) of 13-yearold swimmers and show their ability as biologically youngerlate mature or older olderearly mature, to develop fast 60-s oxygen uptake (𝑉 ̇𝑂2 ) kinetics and tethered swimming strength. Also, the interplay between swimming strength, 𝑉 ̇𝑂2 , and 400-m front crawl race performance was examined.The study involved 36 competitive young male swimmers (metrical age: 12.9 ± 0.56 years). Depending on BA examination, the group was divided into early mature (BA: 15.8 ± 1.18 years, n =13) andlate mature (BA: 12.9 ± 0.60 years, n = 23) participants, especially for the purpose to compare tethered swimming indices i.e. average values of force (Fave) and 𝑉 ̇𝑂2 (breath-by-breath analysis) kinetics indices, measured simultaneously in 1-minute tethered front crawl swimming. From the 400-m racing stroke rate, stroke length kinematics was retrieved.In 1-minute tethered front crawl test, early mature swimmers obtained higher results of absolute values of 𝑉 ̇𝑂2 and Fave. Conversely, when 𝑉 ̇𝑂2 was present relatively to body mass and pulling force (in ml•min -1 •kg -1 •N -1 ), late mature swimmers showed higher 𝑂 2 relative usage. Late mature swimmers generally exhibited slower increase in 𝑉 ̇𝑂2 during first 30 s of 60. 𝑉 ̇𝑂2 , Fave, BA, and basic swimming kinematic stroke length were significantly interrelated and influenced 400-m performance.1-minute tethered swimming revealed significant differences in the homogeneous calendar age / heterogeneous BA group of swimmers. These were distinguished by higher level of 𝑉 ̇𝑂2 kinetics and pulling force in early mature and lower efficiency per unit of body mass per unit of force aerobic system in late mature peers. The higher 𝑉 ̇𝑂2 kinetics and tethered swimming force were further translated into 400-m front crawl speed and stroke length kinematics.